Os projetos de letramento e os desafios da prática de leitura e escrita no Ensino Fundamental II - CARDOSO, Marta Sacramento (2019)
This paper aims to present literacy projects as a systematic proposal for the challenges of reading and writing practice in elementary education II, in addition to understanding the concepts of literacy and literacy. The work is developed through a bibliographical review, where some authors of the area were taken as a base, which approach on the subject in question. The use of the literacy project contributes to understanding, along with the autonomous interpretation of the texts read and leads the teacher to realize the relevance of developing independent, critical and reflective readers. Thus, in order for the student to identify with this practice, the teacher must do it to a reading and writing activity that presents meaning and that is in accordance with the needs of the student. Therefore, literacy projects can respond significantly to the challenges of reading and writing.